Prices for veterinary care of dogs, cats, and horses in Sweden and Norway: comparisons between corporate chain, government-run, and independent clinics - Egenvall, Agneta; Valle, Paul S.; Hoffman, Ruben; Höglund, Odd V.; Byström, Anna; Lönnell, Cecilia; Bonnett, Brenda N. (Frontiers in Veterinary Science, 2025)
IntroductionIn a 10–15-year period, veterinary clinics in Sweden and Norway, as elsewhere, have undergone widespread corporatisation. High veterinary care costs have received attention in the lay press and from competition authorities. Whether corporate chains and independent clinics differ in price levels and how clinic characteristics, such as on-call service, affect pricing is not well-documented. The aim was to analyse prices levels and price changes for various diagnoses/procedures for dogs, cats, and horses from clinics in Norway and Sweden and to examine the influence of affiliation (corporate chain, government-run, or independent), extraction date, and clinic characteristics (e.g., on-call service) on prices.Materials and methodsData from a price comparison site were extracted five times between 2 January 2023 and 2 January 2024. Prices for procedures such as vaccinations, gonadectomy, euthanasia, emergency care, diagnostic imaging, certification, and planned surgery were included. Descriptive statistics and mixed models were used to analyse effects of affiliation (Anicura, The Swedish District Vet Officers (DV), Dyrenes venn, Empet, Evidensia, Vettris, and independent), clinic characteristics (animal hospital or not, on-call service, and number of hours open Mon-Fri), and extraction date.ResultsPrices were analysed for 37 procedures (16 dogs, 11cats, and 10 horses) from 771 clinics, of which 502 (65%) were independent. Most clinics with corporate affiliation belonged to Evidensia and Anicura. In statistically significant comparisons, their prices were generally higher than those from the independent group. For Anicura, the median annual price increase (in Euro) was 8%, DV 5%, Dyrenes venn 53%, Empet 12%, Evidensia 15%, Vettris 7%, and the independent group 6%. Multivariable results generally corroborated the descriptive figures.DiscussionTargeting a range of procedures in two nearby countries, veterinary care prices varied with country, clinic characteristics, and affiliation. Clinics belonging to corporate chains charged higher prices than independent clinics. Most prices increased over the year. Possible reasons for the differences between clinics are investments in equipment or number of staff, expenditure on continued education of staff, or different demands for profit. Increased price transparency within veterinary care might reduce the impact of high prices and perhaps also limit price increases.